The Critical Editing of a Musical Work on the Basis of Incomplete Performance Material: Scheibe’s Second Passion Cantata, ‘Sørge-Cantate ved Christi Grav’ (1769) - Hauge, Peter (Danish Yearbook of Musicology, 2016)
When dealing with the critical editing of music of the eighteenth century, it seems fairly easy to select the composer’s ink fair manuscript as copy text – that is, if such a manuscript has survived. In a few cases, however, also the original performance material is available. The article argues that it is important to take into account the instrumental parts and use them actively in the editing process as they reveal a different set of contexts to that of the ink fair copy scores. Scheibe’s Passion Cantata of 1769 is used as an example of the various problems an editor encounters for, since a contemporary score has not survived, it is necessary to employ the performance material. In addition, the set of parts is incomplete forcing the critical editor to reconstruct the tenor part basing it on the cue notes in the harpsichord and violin parts, for instance. Overall, the material creates a number of intricate problems since it contains contradictory information on performance practice, and the editor has therefore to make some diffi cult choices.